Mental Health Knowledge, Self-Efficacy and Intention to Seek Help in Undergraduate students. How does it Influence? - Yulianti, Padmi Dhyah; Rakhmawati, Dini; Suyati, Tri; Hidayati, Richma; Kusmanto, Agung Slamat (Kuras Institute, 2024)
Mental health in the younger generation is essential to have. However, guidance and counseling undergraduate students who face mental health problems are not all willing to seek help. The low intention to seek help among guidance and counseling undergraduate students is thought to be influenced by a lack of knowledge about mental health and low self-efficacy. The condition of not seeking help results in losses for oneself, the community and the nation's future. The research aims to determine the influence of mental health knowledge and self-efficacy on intentions to seek help. The research used a quantitative design and data analysis using linear regression assisted by SPSS 26. The population of this research is guidance and counseling students. Researchers used purposive sampling and obtained 194 respondents willing to participate in the research. Researchers used three instruments. On the Mental Health Knowledge Schedule scale, the validity level moves from .391 - .870 with a reliability of .896. The general self-efficacy scale with the validity value moves from .450 - .731 and a reliability of .868. The intention to seek help scale with scores ranging from .668 - .845 and a reliability of .887. The research results are: (1) there is an influence between mental health knowledge and intention to seek help, (2) there is no influence between self-efficacy and intention to seek help, (3) there is a correlation between mental health knowledge and self-efficacy, (4) there is no influence between mental health knowledge and self-efficacy on intention to seek help. Suggestions for further research need to reduce the stigma of mental health problems, expand access to mental health assistance and increase undergraduate students' trust in the professional competence of mental health professionals in the educational environment so that undergraduate students are willing to take advantage of access to assistance.